Exploring drivers of modern Hanfu purchase in digital commerce: A mixed-methods perspective - Hao Li; Yucheng Ding; Yuhang Wu; Jiake Ye (PLoS ONE, 2025)
The rapid growth of the modern Hanfu market, driven by digital commerce and social media, has increased the interest in understanding consumer purchase intentions. This study investigates the key factors influencing online purchase intentions for modern Hanfu by integrating text mining, grounded theory, and quantitative analyses. A dataset of 5,992 consumer reviews from major Chinese e-commerce platforms was analyzed using natural language processing techniques to extract critical themes. Additionally, a structured survey (n = 344) was conducted to develop and validate a measurement scale for assessing the key determinants of purchase intention. The findings reveal that co-design has the strongest influence on purchase intention (β = 0.252), followed by website attractiveness (β = 0.235) and product quality (β = 0.160). Despite product quality being a dominant theme in consumer reviews, its impact on the quantitative model is moderate (β = 0.160). Social media engagement and cultural identity emerge as significant but less frequently discussed factors, while merchant service has the weakest effect (β = 0.145). This study contributes to the literature by integrating cultural identity and co-design into purchase intention models, offering theoretical insights into heritage-driven fashion consumption. Future research should explore demographic variations, cross-cultural comparisons, and longitudinal trends to further refine our understanding of modern Hanfu purchase behavior. These results suggest that the top priority of modern Hanfu brands in their marketing management activities is to encourage and promote consumer engagement. Optimizing website design, improving product quality, considering social media strategies, tapping into the essence of ethnic culture, and enhancing customer service are also important.